Gene expression profiling in soybean under aluminum stress: genes differentially expressed between Al-tolerant and Al-sensitive genotypes - Duressa, Dechassa; Soliman, Khairy M.; Taylor, Robert W.; Chen, Dongquan (Scientific Research Publishing, 2011)
It is well documented that aluminum (Al) toxicity is the most important constraint to crop production on acid soils and soybean is one of the most Al sensitive plant species. To advance our understanding of the molecular and genetic mechanisms of Al-tolerance in soybean we compared root tip (1 cm long) transcriptome profiles of an Al-tolerant (PI 416937) and Al-sensitive (Young) soybean genotypes using a combination of DNA microarrays and quantitative real-time PCR gene expression profiling technologies, in a time-course experiment (2, 12, 48, 72 h post Al treatment). We observed many genes differentially expressed between the two genotypes in constitutive and non-constitutive manner. The most likely candidate Al-tolerance genes expressed at high level include the previously reported transcription factors, auxin down regulated-like protein (ADR6-like) and, basic leucine zipper (bZIP 94), sulfur transmembrane transport protein and lipid transfer protein; and several novel genes that include rare cold inducible protein (RCI2B ), GPI-transamidase, malonyl-COA: Isoflavone 7-O-glucoside-6"-O-malontransferase, a cell proliferation protein (WPP2), oleosin protein, pectinestrease inhibitor, and impaired sucrose induction1; whereas genes negatively correlated with Al-tolerance, namely cellulose synthase and calcium transporters were down regulated in Al-tolerant PI 416937 compared to the Al-sensitive Young. The possible mechanisms of how these genes contribute to Al-tolerance trait are discussed. In conclusion, transcriptome profile comparisons of Al-tolerant and Al-sensitive soybean genotypes revealed novel putative Al-tolerance genes. These genes deserve further functional characterization for eventual utilization in developing soybean germplasm adapted to high aluminum soils.
Keywords: Soybean; Al Tolerance; Gene Expression; Microarray